2011
DOI: 10.3109/03009742.2010.548827
|View full text |Cite
|
Sign up to set email alerts
|

Resistin is linked to inflammation, and leptin to metabolic syndrome, in women with inflammatory arthritis

Abstract: The results show that high resistin levels are associated with arthritis independently of MetS, whereas leptin is increased only in arthritis patients with MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…Records after duplicates removed (n = 31) [22] showed that leptin levels were increased only in patients with RA and concomitant diagnosis of metabolic syndrome (MetS). Kang et al (2013) [23] demonstrated that TNF-α was positively associated to leptin and the latter was associated with various metabolic risk factors, including insulin resistance.…”
Section: Leptinmentioning
confidence: 99%
See 1 more Smart Citation
“…Records after duplicates removed (n = 31) [22] showed that leptin levels were increased only in patients with RA and concomitant diagnosis of metabolic syndrome (MetS). Kang et al (2013) [23] demonstrated that TNF-α was positively associated to leptin and the latter was associated with various metabolic risk factors, including insulin resistance.…”
Section: Leptinmentioning
confidence: 99%
“…The authors found that the level of resistin in serum did not differ between patients and controls, but observed that serum resistin were positively associated with CRP levels in RA patients, suggesting a pro inflammatory action of this cytokine. Kontunen et al (2011) [22] reported that high levels of resistin are associated with RA, regardless of the presence of MetS. Fadda et al (2013) [37] compared resistin levels in serum and synovial fluid of patients with RA and osteoarthritis and found higher levels in patients with RA.…”
Section: Resistinmentioning
confidence: 99%
“…Kontunen et al assessed leptin levels in patients with arthritis and MetS. Their results showed higher leptin levels in subjects with arthritis and MetS than arthritis patients without MetS [56]. This suggests that leptin is associated with MetS but not directly with arthritis, although a marked increase in plasma levels of leptin in patients with RA was noted [57].…”
Section: Leptinmentioning
confidence: 99%
“…In other study, Kontunen et al assessed adiponectin levels in patients with arthritis and MetS. Their results showed lower adiponectin levels in subjects with arthritis and MetS than arthritis patients without MetS [56]. Furthermore, Gonzalez-Gay et al suggested that low circulating adiponectin levels may be implicated in the development of CVD associated with RA.…”
Section: Adiponectinmentioning
confidence: 99%
“…As many studies have already suggested, PPARs might be an important link between these two complex systems, and as shown in the present study, PPAR agonists have anti-inflammatory properties in classical inflammatory models. It has been shown that a good treatment of metabolic diseases reduces the low-grade inflammation associated with obesity [38]. But could the modification of metabolic pathways reduce the inflammatory responses associated to classical inflammatory diseases?…”
Section: Discussionmentioning
confidence: 99%